2016
DOI: 10.1037/xge0000190
|View full text |Cite
|
Sign up to set email alerts
|

Reflexive intergroup bias in third-party punishment.

Abstract: Humans show a rare tendency to punish norm-violators who have not harmed them directly-a behavior known as third-party punishment. Research has found that third-party punishment is subject to intergroup bias, whereby people punish members of the out-group more severely than the in-group. Although the prevalence of this behavior is well-documented, the psychological processes underlying it remain largely unexplored. Some work suggests that it stems from people's inherent predisposition to form alliances with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 104 publications
(132 reference statements)
2
58
0
Order By: Relevance
“…A third research direction would be to examine whether young children would tolerate harsher punishments for outgroup wrongdoers compared with ingroup wrongdoers. Previous research on this issue with adults and older children has yielded mixed results (38), with some reports indicating harsher punishments for outgroup wrongdoers (34,35,37,64,73,74), some indicating harsher punishments for ingroup wrongdoers (75), and some indicating similar punishments for ingroup and outgroup wrongdoers (36,66,76). To study this issue with young children, our puzzle scenario could be modified to involve a much harsher punishment: Imagine that instead of throwing away the final piece of the puzzle, the bystander now destroyed each and every piece of it.…”
Section: Discussionmentioning
confidence: 99%
“…A third research direction would be to examine whether young children would tolerate harsher punishments for outgroup wrongdoers compared with ingroup wrongdoers. Previous research on this issue with adults and older children has yielded mixed results (38), with some reports indicating harsher punishments for outgroup wrongdoers (34,35,37,64,73,74), some indicating harsher punishments for ingroup wrongdoers (75), and some indicating similar punishments for ingroup and outgroup wrongdoers (36,66,76). To study this issue with young children, our puzzle scenario could be modified to involve a much harsher punishment: Imagine that instead of throwing away the final piece of the puzzle, the bystander now destroyed each and every piece of it.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with these findings, however, Buckholtz et al (2015) found that disrupting the DLPFC via transcranial magnetic stimulation has, compared to sham, the effect of decreasing the rate of punishment of norm-transgressors in hypothetical scenarios. Yudkin, Rothmund, Twardawski, Thalla and Van Bavel (2016) found that cognitively loaded participants punish out-group members more severely than in-group members. Artavia-Mora, Bedi and Rieger (2017) found that time delay, compared to time pressure, does not affect third-party punishment in a field experiment in which participants had the possibility of withholding help (by not returning a lost glove) from someone who had litter.…”
Section: Review Of the Empirical Evidence On Negative Reciprocitymentioning
confidence: 96%
“…Main result Olschewski et al (2018) UG responder Load has no effect on rejection of low offers Ego depletion studies Anderson & Dickinson (2010) UG responder Sleep restriction increases minimum acceptable offers Crockett et al (2008) UG responder Serotonin depletion increases rejection rates of unfair offers Crockett et al (2010a) UG responder Serotonin depletion increases rejection rates of unfair offers Crockett et al (2010b) UG responder Enhancing serotonin decreases rejection rates of unfair offers Halali et al (2014) UG responder Ego depletion increases rejection of low offers Morewedge et al 2014UG responder Alcohol intoxication increases rejection of low offers Liu et al 2015UG responder Ego depletion increases rejection of low offers Achtziger et al 2016UG responder Ego depletion decreases rejection of low offers Clark & Dickinson (2017) PGG with punishment Sleep restriction has no effect on punishment Achtziger et al (2018) UG responder Ego depletion has no effect on rejection of low offers Neurostimulation studies Knoch et al (2006) UG responder Disruption of rDLPFC decreases rejection of low offers, compared to disruption of lDLPFC Knoch et al (2008) UG responder Disruption of rDLPFC decreases rejection of low offers, compared to sham Baumgartner et al 2011UG responder Disruption of rDLPFC decreases rejection of low offers, compared to disruption of lDLPFC 2-response paradigm studies Bago et al (2019) UG responder Deliberation has no effect on rejection rates: most rejection choices under deliberation are already Measure Main result rejection choices under intuition 3P-punishment Time constraint studies Wang et al (2011) TG with punishment Pressure increases punishment compared to Delay Artavia-Mora et al 2017Field experiment Pressure has no effect on punishment, compared to Delay Cognitive load studies Yudkin et al (2016) SG with punishment Load makes people punish outgroup members more severely than ingroup members Ego depletion studies Liu et al (2015) UG with punishment Ego depletion increases punishment of unfair offers Neurostimulation studies Buckholtz et al (2015) Punishment norm violators in vignettes Disruption DLPFC decreases punishment, compared to sham Anti-social punishment Conceptual prime studies Pfattheicher et al (2017) PGG with punishment Intuition increases antisocial punishment, compared to Baseline. Inhibiting Intuition decreases anti-social punishment, compared to Baseline.…”
Section: Measurementioning
confidence: 99%
“…In contrast with these findings, however, Buckholtz et al (2015) found that disrupting the DLPFC via transcranial magnetic stimulation has, compared to sham, the effect of decreasing the rate of punishment of norm-transgressors in hypothetical scenarios. Yudkin, Rothmund, Twardawski, Thalla and Van Bavel (2016) found that cognitively loaded participants punish out-group members more severely than in-group members. Artavia-Mora, Bedi and Rieger (2017) found that time delay, compared to time pressure, does not affect third-party punishment in a field experiment in which participants had the possibility of withholding help (by not returning a lost glove) from someone who had litter.…”
Section: Review Of the Empirical Evidence On Negative Reciprocitymentioning
confidence: 96%